PENGELOLAAN DANA DAERAH DALAM PENANGGULANGAN STUNTING DI KABUPATEN PEMALANG TAHUN 2022 - Maharani, Putri Widiyana; Mutiarin, Dyah; Saputro, Muhammad Noor Cahyadi Eko (Prosiding University Research Colloquium, 2023)
Stunting is a nutritional problem that has not been properly addressed. The problem of stunting cannot be remedied solely through incidental and partial measures. It must be addressed comprehensively from its roots; hence, it is critical to do research focused on finding a solution. The goal of this study is to determine the scope of the problem and how to combat stunting in Pemalang Regency. The research approach employed was qualitative, with data collected through interviews, observation, and literature reviews. The study comprised 10 villages with a high number of stunting cases: Jatingarang Village, Banjarmulya, Gondang, Kaligelang, the Islamic Boarding School, Kreyo, Banyumudal Village, Sima, Walangsanga, and Sugihwaras Village. The study's findings indicated that the program for combating malnutrition in Pemalang Regency had been properly resolved, with continual alignment of coaching and routine programs, and was also supported by enough money from the Health Operational Assistance, the Regional Government Budget, and the Revised Regional Government Budget. The participation of the Health Office in the stunting prevention program was listed in the "good" category for reducing the prevalence of nutritional disorders in Pemalang Regency. The Health Office's intervention was more targeted in its approach, ranging from treating adolescents to caring for the growth and development of toddlers. Cross-sectoral regional organizations carried out sensitive interventions. It is hoped that with the involvement of the Health Service and other sectors, it will be possible to minimize the stunting rate in Pemalang Regency during its implementation.